Spatial distribution and temporal trends of cyclic and linear siloxanes in sediment from semi-enclosed and industrialized bays of Korea, in 2013 and 2021 - Chen, Wenming; Kang, Yujin; Lee, Hyun-Kyung; Lim, Jae-Eun; Lee, Moonjin; Moon, Hyo-Bang (Frontiers in Marine Science, 2023)
Although siloxanes are contaminants of emerging concerns, limited studies have been conducted on contamination and time trends in siloxanes from aquatic environments worldwide. To date, most previous studies have focused on the environmental relevance of cyclic siloxanes in coastal environments. In the present study, cyclic and linear siloxanes were measured in sediment collected from semi-enclosed bays in Korea in 2013 and 2021 to assess occurrence, spatial distribution, temporal trends, and ecological risks. Almost all siloxanes were detected in all sediment samples, indicating continuous contamination for the last decade. The concentrations of cyclic siloxanes in sediment were approximately two times higher than those of linear siloxanes. Decamethylcyclopentasiloxane (D5) and dodecamethylcyclohexasiloxane (D6) were predominantly detected in all sediment samples, possibly due to their high consumption and strong resistance. The overall concentrations of siloxanes in sediment gradually decreased from inner to outer parts of the bays, suggesting that industrial activities largely contributed to siloxane contamination. Moreover, the highest concentrations of siloxanes in both sampling years were observed in sediment near the outfall of wastewater treatment plant, implying a potential source in the coastal environment. Siloxane concentrations in sediment were significantly correlated with sedimentary organic carbon. The concentrations of siloxanes in sediment were not significantly different between 2013 and 2021, indicating ongoing contamination. The concentrations of D5 and D6 in our sediment samples showed a limited potential to pose a threat to benthic organisms.